2018
DOI: 10.1002/2017gb005843
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Explicit, Regional‐Scale Simulation of Lake Carbon Fluxes

Abstract: Lakes are areas of intense biogeochemical processing in the landscape, contributing significantly to the global carbon cycle despite their small areal coverage. However, current large‐scale estimates of lake biogeochemical fluxes are all generated by multiplying a mean observed areal rate by regional or global lake surface area, which ignores important heterogeneous spatial and temporal processes that regulate lake carbon cycling. We have developed a process‐based model that integrates core scientific knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 98 publications
(193 reference statements)
0
22
0
Order By: Relevance
“…A direct application of our integrated modeling framework to the ecological field has been detailed in Zwart et al. (), which used the hydrologic fluxes simulated in this study to investigate lake carbon processing for the same set of inland lakes. In this study, we also showed that our model can easily take advantage of new data sources to improve model performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A direct application of our integrated modeling framework to the ecological field has been detailed in Zwart et al. (), which used the hydrologic fluxes simulated in this study to investigate lake carbon processing for the same set of inland lakes. In this study, we also showed that our model can easily take advantage of new data sources to improve model performance.…”
Section: Discussionmentioning
confidence: 99%
“…Our final dataset included 3,692 lakes and reservoirs within the NHLD region (see Zwart et al. for more information on dataset inspection). We simulated each lake one time within its respective subdomain across the modeling time period and synthesized the results of all subdomains into a single regional dataset for subsequent analysis of the NHLD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lake heat budget, constituent load, and biogeochemical models were driven by the hydrologic output from the coupled surface water and groundwater model and parameterized exactly as described in Zwart et al (2018) with altered driving data from the climate change scenarios as described above. Our lake heat budget model used mass balance equations (Lenters et al, 2005) and functions from the R package LakeMetabolizer to model lake water temperature during the open-water period as in Zwart et al (2018). The constituent loading model uses land cover, long-term data, and simulated water budgets from our coupled hydrologic model to estimate inflowing dissolved organic carbon (DOC), dissolved inorganic carbon (DIC), terrestrial particulate organic matter, and dissolved inorganic phosphorus to each lake Zwart et al (2018).…”
Section: Lake Heat Budget Constituent Load and Biogeochemical Modelsmentioning
confidence: 99%
“…Our lake heat budget model used mass balance equations (Lenters et al, 2005) and functions from the R package LakeMetabolizer to model lake water temperature during the open-water period as in Zwart et al (2018). The constituent loading model uses land cover, long-term data, and simulated water budgets from our coupled hydrologic model to estimate inflowing dissolved organic carbon (DOC), dissolved inorganic carbon (DIC), terrestrial particulate organic matter, and dissolved inorganic phosphorus to each lake Zwart et al (2018). For this analysis, we focused on the impact of climate change scenarios on lake C fluxes and productivity.…”
Section: Lake Heat Budget Constituent Load and Biogeochemical Modelsmentioning
confidence: 99%